Separating and quantifying the distinct impacts of El Niño and sudden stratospheric warmings on North Atlantic and Eurasian wintertime climate ... - Oehrlein, Jessica; Chiodo, Gabriel; Polvani, Lorenzo M. (ETH Zurich, 2019)
Sudden stratospheric warmings (SSWs) significantly influence Eurasian wintertime climate. The El Niño phase of the El Niño–Southern Oscillation (ENSO) also affects climate in that region through tropospheric and stratospheric pathways, including increased SSW frequency. However, most SSWs are unrelated to El Niño, and their importance compared to other El Niño pathways remains to be quantified. We here contrast these two sources of variability using two 200‐member ensembles of 1‐year integrations of the Whole Atmosphere Community Climate Model, one ensemble with prescribed El Niño sea surface temperatures (SSTs) and one with neutral‐ENSO SSTs. We form composites of wintertime climate anomalies, with and without SSWs, in each ensemble and contrast them to a basic state represented by neutral‐ENSO winters without SSWs. We find that El Niño and SSWs both result in negative North Atlantic Oscillation anomalies and have comparable impacts on European precipitation, but SSWs cause larger Eurasian cooling. Our ... : Atmospheric Science Letters, 20 (7) ...